The Cambridge companion to Bede - DeGregorio, Scott (Cambridge companions to authors, 2010)
"The introduction of Christianity affected the organisation of power. A comparable development is seen most powerfully in the career of Wilfrid: the church had produced a new kind of potentate, an ecclesiastical one, with a status and influence transcending the boundaries of a single kingdom"--Provided by publisher